Prevalence of Diabetic Foot Ulcer and Associated Factors among Adult Diabetic Patients on Follow-Up Clinic at Jimma Medical Center, Southwest Ethiopia, 2019: An Institutional-Based Cross-Sectional Study - Daba Abdissa; Tesfaye Adugna; Urge Gerema; Diriba Dereje (Journal of Diabetes Research)
Background. Diabetic foot ulceration is a devastating complication of diabetes mellitus and is a major source of morbidity and mortality. So far, there are few published data on diabetic foot ulcers and its determinants among diabetic patients on follow-up at Jimma Medical Center. Hence, the aim of this study was to assess the prevalence of diabetic foot ulcer and its determinants among patients with diabetes mellitus at Jimma Medical Center. Methods. A hospital-based cross-sectional study was conducted from June 1 to August 30, 2019, and systematic random sampling technique was applied. The total number of study subjects who participated in the study was 277. Data were collected using an interview-administered structured questionnaire. Data were entered into EpiData version 3.1 and exported to SPSS version 20 software for analysis. Analysis was done using descriptive statistics and logistic regression. A variable having a p value of <0.25 in the bivariate model was subjected to multivariate analysis to avoid confounding the variable’s effect. Adjusted odds ratios (AOR) were calculated at 95% confidence interval and considered significant with a p value of ≤0.05. Result. The mean of age of participants was 50.1±14.19 years. More than three-fourths of participants (82.7%) were type 2 DM. The mean duration of diabetic patients was 6.00±5.07 years. The prevalence of diabetic foot ulcer was 11.6% among study participants. According to multivariate logistic regression analysis, previous history of ulceration (AOR=5.77; 95% CI: 2.37, 14.0) and peripheral neuropathy (AOR=11.2; 95% CI: 2.8, 44.4) were independent predictors of diabetic foot ulcer. Conclusion. The prevalence of diabetic foot ulcer was 11.6%. Previous history of ulceration and peripheral neuropathy were associated with diabetic foot ulcer. The health care providers are recommended to thoroughly give emphasis during follow-up of patients who had previous history of ulceration and peripheral neuropathy in order to decrease the occurrence of diabetic foot ulcer.